Navigating uncertainty and complexity: Higher education and the dilemma of employability - Bennett, Dawn; Richardson, S.; Mahat, M.; Coates, H.; MacKinnon, P. (Higher Education Research and Development Society of Australasia, Inc, 2015)
This paper reinforces growing social and economic demands for graduates who can navigate the uncertainty and complexity of rapidly transforming employment contexts. This aim is first addressed with an overview of the research on employability and the changing nature of work and employment. This is followed with a discussion of employability and career development within higher education. The article concludes by considering the implications for higher education institutions. Recommendations include the development of graduate employability measures that record multiple employments and the refinement of employability models. The authors challenge higher education institutions to place the development of self and career at the core of every program.